2012
DOI: 10.1155/2012/947694
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Incontinence: Prevalence, Severity, and Quality of Life Data from an Outpatient Gastroenterology Practice

Abstract: Background. The prevalence of fecal incontinence varies tremendously as a result of inadequate data collection methods. Few office-based studies have assessed the prevalence of fecal incontinence and none have looked at modifiable risk factors or effect on quality of life. Design, Settings, Patients, and Main Outcome Measures. Five hundred patients who visited our inner city, university-based gastroenterology practice, were asked about symptoms of fecal incontinence. We also retrospectively reviewed 500 chart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 23 publications
2
30
0
8
Order By: Relevance
“…In fact, more than 4 additional Wexner scale points were necessary to overcome the effect of being female. Our results are consistent with those of Alsheik et al, 7 although in that study all four FIQL subscales were combined, and partially with Cohan's, 32 who found male gender to be significantly associated with improved coping and embarrassment scores. However, other studies did not find significant differences between the sexes 30 or reported an improved life style scoring associated with being female.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In fact, more than 4 additional Wexner scale points were necessary to overcome the effect of being female. Our results are consistent with those of Alsheik et al, 7 although in that study all four FIQL subscales were combined, and partially with Cohan's, 32 who found male gender to be significantly associated with improved coping and embarrassment scores. However, other studies did not find significant differences between the sexes 30 or reported an improved life style scoring associated with being female.…”
Section: Discussionsupporting
confidence: 93%
“…Although QoL for patients with fecal incontinence has been researched, little has been said about the impact of gender. Few studies of community-dwelling patients have tried to explore this aspect and results have varied: one study did not find differences between genders, 30 another found slightly better QoL in women, 31 in a third, higher coping and embarrassment scores were associated with men, 32 and a fourth study 7 reported that women had a significantly lower average QoL; in this latter study, however, the FIQL dimensions most affected were not specified. Knowledge of how gender affects QoL can be of great importance when treating and counseling patients.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Though affecting mostly elderly women, the prevalence of FI in the general population is highly variable, with reports ranging from 0.4% to 18% [2][3][4][5]. The actual prevalence is likely higher than this since many cases remain unreported due to embarrassment.…”
Section: Discussionmentioning
confidence: 99%
“…FI affects both genders but is more prevalent among women, especially the elderly [1]. The overall prevalence is 0.4-18% [2][3][4][5], but the condition is often unreported due to embarrassment, despite significant loss of quality of life [5,6].…”
Section: Introductionmentioning
confidence: 99%